Contemporary CAD/CAM Materials in Dentistry - Tiu, Janine; Belli, Renan; Lohbauer, Ulrich (Current Oral Health Reports, 2019)
Purpose of Review: To present an update on the current CAD/CAM materials in restorative dentistry. Recent Findings: Important contributions are seen in updated mechanical properties of CAD/CAM materials, new insights in lithium silicate systems, and development in translucent zirconia. Many materials are arriving at optimized processing procedures and further development will come from new strategies and systems. Increasing our understanding of CAD/CAM materials will improve their use and indications and drive innovation. Summary: A general update was provided by classifications, mechanical properties, and clinical considerations by providing commentary on recent significant contributions.
CRIS-Team Scopus Importer:2021-04-20
Keywords: CAD/CAM; Dental restorative materials; Glass-ceramics; Mechanical properties; Zirconia